Estudo da dessorção seletiva do corante reativo em carvão ativado - Carvalho, Dayane Samara de (2013)
The textile industries consuming a large quantity of water which generates a high volume of effluent. One of the main characteristics of the intense color of effluent is due to a significant percentage of non-fixed dye to the fabric during the process. Thus, it is essential to remove this color of effluent and one of the techniques that have received special attention due to its efficiency and versatility, is the adsorption on activated carbon. However, so that the process becomes economically viable, it is necessary that the adsorbent can be regenerated after becoming saturated, to be reused in the process. Within this context, the aim of this study was to evaluate the ability of dye desorption of activated carbon and analyze the behavior of the cycles of adsorption / desorption in batch. The study started with the characterization of four activated carbons, which is: babassu, coconut, palm and bone char. The characterizations were carried point of zero charge, adsorption/desorption of N2, FTIR and method Boehm. The adsorption capacity of these activated carbons was evaluated, and the bone char was the one with the most capacity of approximately 113 mg/g. Thus, this coal was used in the studies desorption. Kinetic and equilibrium studies were performed for the adsorption of the dye on bone char to identify the possible mechanism of adsorption, which may influence the ability of the dye desorption of the activated carbon. The pseudo-first order and Langmuir model were the best fit to experimental data, indicating that diffusion of dye molecules through the boundary layer is the rate limiting step for adsorption and chemisorption occur, which can hinder desorption. Thus, to verify the ability of the dye desorption, the parameters evaluated in the desorption of the dye were contact time, pH of the water and initial concentration of regenerants, and products used to perform the desorption water, NaOH, alcohol methyl, ethyl alcohol and isopropyl alcohol. The initial pH of the water was found to have little influence on the ability of desorption of the dye, and the higher desorption capacity was 2.09 mg/g at pH 12. Tests with NaOH showed that the smaller the concentration the greater the ability desorption, and in 0.01 mol/L NaOH desorbed amount was 3.86 mg/g. The organic solvents showed improved desorption efficiency when diluted with water. Thus, the optimum desorption capacities were obtained with 50% (v / v) isopropyl alcohol, 50% (v / v) ethyl alcohol and 80% (v / v) alcohol methyl, with 21.76, 20.41 and 15.56 mg/g, respectively. Kinetic study for desorption of the dye with isopropyl alcohol and ethyl alcohol were performed, and the model that best fit was the pseudo-second order, which presented the value of the rate constant larger than the adsorption step, due desorption is faster. Experiments to obtain the desorption isotherms were performed at temperatures of 20, 30 and 40 ºC. The desorption isotherms and adsorption of bone char were classified according to Giles et al. (1958) to demonstrate the appearance of a hysteresis due to different classifications of isotherms, and this fact is associated with the irreversibility of the process. Thermodynamic study was also performed, showing that with increasing desorption, there is an increased ?Ho and ?So, indicating that, due to the increased amount desorbed, there is an increased energy and disorder in the system. However, with increasing temperature, a reduction of ?Go, suggesting that with the increase in temperature there is a greater viability of the process. Finally, the adsorption and desorption cycles in batch showed that the dye can bind to the adsorbent by strong interactions and by weak interaction, wherein the strongly adsorbed amount cannot be desorbed while the dye interacted with the adsorbent by weak interactions was able to be desorbed. However, the most desorption percentage obtained was 28% and 30% ethyl alcohol and isopropyl alcohol, respectively, at the temperature of 40 °C and in consequence of the fact that almost all adsorbed amount from the second cycle be desorbed it's can reuse the charcoal in the process.